2009
DOI: 10.1590/s0100-72032009000200001
|View full text |Cite
|
Sign up to set email alerts
|

Alterações cardiotocográficas após analgesia obstétrica combinada raqui-peridural

Abstract: EditorialAs alterações cardiotocográficas observadas durante o trabalho de parto conduzido sob analgesia obstétrica constituem um desafio para obstetras e anestesiologistas. Apesar do grande avanço dessas técnicas para minimizar sua interferência com a evolução do trabalho de parto e manter o bem-estar fetal, ainda existem dúvidas sobre o significado e o manejo das alterações da frequência cardíaca fetal (FCF) subsequentes a esses procedimentos 1,2 . Em particular, a técnica combinada raquiperidural, também co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In fact, during CSE for pain management the rapid onset may produce a transient unbalance of maternal catecholamine level, leading to uterine hyperactivity and fetal heart rate (FHR) abnormalities [60] . In fact, Abrado et al reported that CSE is associated with significantly greater rate of FHR abnormalities, related to the hypertonus of the uterus compared to epidural analgesia [61] . Furthermore, Van de Velde et al connected the FHR with CSE [62] at dosage of analgesia drugs, observing that FHR abnormalities are frequent after administration of 7.5 μg.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, during CSE for pain management the rapid onset may produce a transient unbalance of maternal catecholamine level, leading to uterine hyperactivity and fetal heart rate (FHR) abnormalities [60] . In fact, Abrado et al reported that CSE is associated with significantly greater rate of FHR abnormalities, related to the hypertonus of the uterus compared to epidural analgesia [61] . Furthermore, Van de Velde et al connected the FHR with CSE [62] at dosage of analgesia drugs, observing that FHR abnormalities are frequent after administration of 7.5 μg.…”
Section: Discussionmentioning
confidence: 99%